2018
DOI: 10.4178/epih.e2018022
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from aluminum phosphide poisoning in Kermanshah Province, Iran: characteristics and predictive factors

Abstract: OBJECTIVESAluminum phosphide (ALP), also known in Iran as rice tablets, is one of the most effective rodenticides used to protect stored grain. However, ALP poisoning regularly causes mortality in humans. The aim of this study was to evaluate the characteristics and predictive factors of mortality from ALP poisoning.METHODSThis study evaluated all patients with ALP poisoning referred to Imam Khomeini Hospital in Kermanshah Province, Iran from 2014 to 2015. For each patient, the following information was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 20 publications
6
27
1
Order By: Relevance
“…Finally, the patients proceed to multi-organ failure and death within the first 24 to 48 hours after poisoning. Similar findings were also reported in many previous studies from different countries (Anger et al, 2000;Nocera et al, 2000;Navabi et al, 2018).…”
Section: Resultssupporting
confidence: 92%
“…Finally, the patients proceed to multi-organ failure and death within the first 24 to 48 hours after poisoning. Similar findings were also reported in many previous studies from different countries (Anger et al, 2000;Nocera et al, 2000;Navabi et al, 2018).…”
Section: Resultssupporting
confidence: 92%
“… 10 One hundred percent CFR with blood pH <7.0 and 100% survival with pH >7.35 was observed by Shadnia et al 11 Navabi et al also demonstrated blood pressure, pH as well as the time interval between ingestion and treatment as significant predictors. 20 Low SBP, metabolic acidosis, and electrocardiographic abnormality were associated with poor outcome in a retrospective study from Egypt. 19 In another Egyptian study from a university hospital, Sheta et al studied the role of echocardiography for predicting the mortality which can detect low ejection fraction resulted from cardiac ischemia and decreased myocardial contractility in AlP poisoning.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies have looked at numerous demographic, physiological, and biochemical parameters to access the severity of AlP poisoning; however, none of these factors, either alone or in combination, have been validated. 10 , 11 , 14 – 20 A simplified prognostic or severity scoring system, preferably clinical, is the need of the hour. In this study, we have looked at various predictors of CFR and sought to develop a precise and simple outcome prediction score for acute AlP poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium phosphide (ALP), also known as rice tablet in Iran, is used throughout the world as a fumigant, rodenticide, pesticide, and insecticide for the control of insects and rodents through the fumigation of agricultural commodities, animal feeds, and processed foods [1,2]. In many developing countries, especially in Asia, ALP causes a high fatality rate (60-90%) [3,4]. A recent 8-year study showed an increased incidence of fatal ALP poisoning from 2006 to 2013 in Tehran, which included 2007 cases of phosphine poisoning-related deaths [5].…”
Section: Introductionmentioning
confidence: 99%
“…A recent 8-year study showed an increased incidence of fatal ALP poisoning from 2006 to 2013 in Tehran, which included 2007 cases of phosphine poisoning-related deaths [5]. The majority of ALP poisoning cases in Iran involve intentional acts of suicides although some accidental cases of ALP poisoning occur through the occupational exposure [3].…”
Section: Introductionmentioning
confidence: 99%